2016
DOI: 10.1111/trf.13653
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of high‐quality cord blood units

Abstract: This study provides elements for a model that allows an efficient selection of UCB donors, prioritizing candidates who have a better chance to lead to an optimized use of cord blood cells units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Maternal age at delivery has been analyzed in 28 of 71 articles . In most articles, no significant correlation was found with UCB volume, TNCs, CD34+ cells, or CFU (Fig.…”
Section: Highlighted Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal age at delivery has been analyzed in 28 of 71 articles . In most articles, no significant correlation was found with UCB volume, TNCs, CD34+ cells, or CFU (Fig.…”
Section: Highlighted Factorsmentioning
confidence: 99%
“…During a Cesarean, the newborn infant is usually positioned higher than the placenta, thus favoring the downflow of blood into the placental cord and consequently into the umbilical compartment. Moreover, the placenta is expelled manually and more rapidly than after vaginal delivery, which may reduce the possibility of blood clot formation . Hemodilution occuring during Cesarean delivery may also be a reason for the increased volume, whereas the TNC increase in vaginal delivery is related to the fetal stress response, which increases cytokine levels in the fetal circulatory system …”
Section: Highlighted Factorsmentioning
confidence: 99%
“…In addition, several other factors in the perinatal period also exert a strong influence on UCB‐SCs. It has been shown that greater placental weight and umbilical cord length are associated with greater volumes of extracted UCB and a greater quantity of UCBCs, including hematopoietic stem cells, TNCs, and CFUs (Ballen et al, ; Page et al, ; Santos et al, ). Shorter gestation tends to result in more hematopoietic stem cells and a higher CFU count, but a lower volume of UCB and a lower TNC count (Manegoldbrauer et al, ).…”
Section: Sources Of Ucb‐scs In Preterm Infantsmentioning
confidence: 99%
“…They can also be found in cord blood (CB) in a similar frequency to PB (2), but the small volume in CB units represents the difficulty in obtaining suitable numbers of NK cells needed for clinical use (3). Human NK cells are phenotypically described as CD3 − CD56 + cells within the lymphocyte population (4), and they are classified as a subset within the group 1 of innate lymphocyte cells, capable of producing IFN-γ, and exert cytotoxicity (5).…”
Section: Introductionmentioning
confidence: 99%